Fantasy in children's animated commercials: a comparative study of Nestle's television advertising in South Africa - Naran, Ajay (My University, 2012)
With the invention and development of media technologies such as radio, television and the Internet, advertisers have welcomed and embraced these advancements for the purpose of selling products to the masses. Advertisers have considered television to be an effective and popular technology for marketing and communication; and animation has been used extensively in advertising. My proposed research will attempt to explain the reason for the widespread use of animation in television advertising aimed at children. Thus, through an examination and understanding of historical and contextual factors that may have influenced two South African animated television commercials, my research will attempt to highlight why the medium of animation was utilised and thought to be appropriate and appealing to children.
M.A., Faculty of Humanties, University of the Witwatersrand, 2011